The Outstaring Eye: Belfast in John Duncan’s photographs - Michaela Marková (Revue LISA)
This essay is devoted to the photographic work of John Duncan (1968-), born in Belfast, whose pictures explore the townscapes of his home city and its immediate environment, focusing especially on the visual signs of post-Troubles and the Ceasefire era. Our contention is that Duncan’s photographs show deep changes in the city and document the way the population is allowed or not to build an intimate relationship with them. They shed light on the existing tension between hopes for Peace and the lasting force of partisan identification, and underline the real changes Belfast is undergoing, despite sectarian divisions and through political will. We will focus on the way in which Duncan’s work reflects today’s social and political realities of Northern Ireland.